Motivasi dan Hambatan Kerja Aparatur Sipil Negara pada Sistem Work From Home (WFH) : (Studi pada Salah Satu Kementerian Di Jakarta) - Naurah Lisnarini; Gessan Kurnia Dewi (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
Indonesia is one of the countries affected by the COVID-19 pandemic, this outbreak affects all sectors, both formal and informal. To break the chain of the spread of the corona virus, the government is motivated to issue new regulations that must be applied by the entire community. Policies related to social distancing have also been implemented, one of the policies issued by the government is working from home or Work From Home (WFH). This policy is carried out in companies and government agencies (ASN). Of course, there are many work adjustments experienced by ASN during WFH, especially one of the Ministries in Jakarta which is the object of research. This research is a qualitative research with a case study approach. Data collection was obtained from semi-structured interviews with 5 informants consisting of staff from different departments and Division Heads. This study aims to explain how employees perform, what obstacles are faced by employees and leaders and how employees can maintain productivity during Work From Home.